All Paths Lead to Rome. Establishing an Italian American Archive of the Visual Arts of the late 1950s and early 1960s - Blandino, Laura (Review of International American Studies, 2017)
Laura Blandino University of Turin Italy All Paths Lead to Rome. Establishing an Italian American Archive of the Visual Arts of the late 1950s and early 1960s This paper examines the role Rome played in the 1950s as an important outpost for the development of a distinct art scene, where the American and the Italian experience had the opportunity to blend with the artists gathering and sharing innovative ideas. It is a part of an ongoing research and it presents and sums up the early stage of the project which focuses mostly on archival sources and interviews with the central figures of this period. This paper, in particular, follows some of the members of this tran-Atlantic community, focusing in particular on the art galleries that fostered an international dialogue. Above all, this paper addresses the fundamental questions concerning whether this period could be considered as an “archive” of Italian and American art. It aims at demonstrating that, though not altogether free from contradictions and misconceptions, the period under study was very fertile in terms of the results of cross-cultural experience.